Sexual dimorphism phenomenon of first record Macrobrachium lar (Fabricius, 1978) from the southern Sukabumi, West Java, Indonesia - RISKA RISMAWATI; MAJARIANA KRISANTI; ACHMAD FARAJALLAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rismawati R, Krisanti M, Farajallah A. 2024. Sexual dimorphism phenomenon of first record Macrobrachium lar (Fabricius, 1978) from the southern Sukabumi, West Java, Indonesia. Biodiversitas 25: 1929-1937. Macrobrachium lar (Fabricius, 1798), commonly known as monkey river prawn, is a widely distributed amphidromous species found in various freshwater habitat, displaying adaptability to different salinities. This habitat diversity often leads to the emergence of cryptic species, particularly in freshwater shrimp. Notably, M. lar exhibits sexual dimorphism. The degree of sexual dimorphism can differ among decapod crustaceans. This study reports the first discovery of M. lar in Sukabumi, West Java, collected in January 2023 from a river tributary in the Cibitung Sub-district with insights into the sexual dimorphism phenomenon. We conducted species confirmation through molecular analyses. We use the Cytochrome Oxidase subunit 1 (COI) gene fragment for molecular analysis. Phylogenetic tree values revealed that the samples we found proved to be M. lar, forming a group with M. lar from the Indian-West Pacific region and M. lar from Pangandaran. However, they were distinct from the outgroups M. idae and M. Lepidactyloides. In this study, we only use the adult sample, which is already well-developed. Morphological analysis indicated that all morphological characters in males were larger than in females, with significant sexual dimorphism observed in the second pereiopod and its parts (ischium, merus, carpus, and palm). Although the body sizes of males and females are significantly different in a positive direction, the most distinguishing feature facilitating the identification of both as the same species is the pattern on the second pereiopod, which has irregular blotches of brownish coloration.